Sensory attributes of native stingless bee honey (Plebeia molesta): first approaches to the characterization and preference of local consumers - Geisa, Melisa Gabriela; Ciappini, María Cristina; Hilgert, Norma Inés (Ethnobiology and Conservation, 2021)
The sensory quality of a food is related to the consumer’s ethno-social and idiosyncratic conditions.  In this study, honeys from three different environments in the Chaco region of Córdoba (Argentina) were described qualitatively and quantitatively by specialized evaluators and rural peasant. Honeys with a wide diversity of sensory attributes were evidenced. The samples from Salinas Coast were characterized by high fluidity, those from Serrano Forest by quantity of crystals, and those from Plain Forest by the greatest persistence of taste. The rural population used some shared descriptors for honeys from similar geographical origin. Most rural consumers distinguished the honey from A. mellifera, Plebeia nov. sp. and P. molesta, which were also the preferred ones. We analyzed the results in relation to the Socio-ecological Theory of Maximization and concluded that the sensory components of P. molesta honeys allow their differentiation according to environment of origin and from honeys of other melliferous insects, which together with farmers´ idiosyncratic factors model the selection of the product.